A detailed investigation of a geological CO2-storage reservoir - Hatland, Anna Maria (UiT The Arctic University of Norway, 2015)
Increased CO2-concentrations within the atmosphere of the Earth have encouraged development of “carbon capture and storage” (CCS). It is important to avoid global warming, and CO2 may be stored within geological formations in the subsurface. This thesis focuses on the possibilities of storing CO2 in a reservoir of Middle Triassic-Middle Jurassic age in The Nordkapp Basin, The Southern Barents Sea. The thesis tries to map out the extent of a reservoir and a cap rock, calculate the amount of injectable CO2, and assess the potential risks of leakage for the CO2-storage complex. The evaluation is based on a migrated 3D-seismic dataset, ST9403, with 7228/7-1A as a reference well. The well penetrates several formations, where the formations of Stø-Tubåen are considered the best reservoir unit, consisting of a homogenous sandstone with good properties. The cap rock constitutes the formations of Hekkingen and Fuglen, which is tight, covering and homogenous. The trap type is linked to extensive salt domes, enclosed by faulted structures. The salt domes are stable and the faults inactive and tight. Possible hazardous, chemical reactions between the salt, the injected CO2 and a Permian carbonate are considered the largest safety risks for the CO2-storage complex.